Development of a sports injury aid and treatment handbook for high school students - Boby Helmi; Rinaldi Aditya; Lusiana Lusiana (Journal Of Sport Education (JOPE), 2023)
(English)This research aims to create a pocketbook for students that focuses on Sports Injury Relief and Treatment in schools. This study is development research based on the Borg and Gall design involving four validators: user lecturers, therapists, massage experts, and media experts. Small scale trial with four students and a large scale with 25 students. The data collected for this research was collected through implementation tests and expert assessments carried out through questionnaires, as well as competency tests carried out through descriptive data analysis. Researchers used 8 out of 10 steps, namely identification of potential and problems, collection of materials, product design, product creation, validation by material experts and media experts, product revision, final product, and limited trials. The subjects in this research were class XI students at Tunas Pelita High School, Binjai City. Small group trials showed that this pocketbook was quite adequate with material at 60%, language readability at 50%, and presentation of the book at 55%. Large group trials showed that this pocketbook was feasible with the material at 87%, language readability at 91%, presentation of the book at 90%, and appearance of the book at 91%. Overall, this paperback is considered decent(Indonesian)Tujuan dari penelitian ini adalah untuk membuat buku saku bagi siswa yang berfokus pada Pertolongan dan Perawatan Cedera Olahraga di sekolah. Studi ini adalah penelitian pengembangan berdasarkan desain Borg and Gall yang melibatkan empat validator: dosen pengguna, ahli terapi, ahli massage, dan ahli media. Uji coba skala kecil dengan empat siswa dan skala besar dengan 25 siswa. Data yang dikumpulkan untuk penelitian ini dikumpulkan melalui uji pelaksanaan dan penilaian ahli yang dilakukan melalui lembar kuesioner, serta uji kompetensi yang dilakukan melalui analisis data deskriptif. Peneliti menggunakan 8 dari 10 langkah yaitu identifikasi potensi dan masalah, pengumpulan bahan, desain produk, pembuatan produk, validasi oleh ahli materi dan ahli media, revisi produk, produk akhir, serta uji coba terbatas. Subyek dalam penelitian ini adalah siswa kelas XI SMA Tunas Pelita Kota Binjai. Uji coba kelompok kecil menunjukkan bahwa buku saku ini Cukup layak dengan segi materi sebesar 60%, keterbacaan bahasa sebesar 50%, dan penyajian buku sebesar 55%. Uji coba kelompok besar menunjukkan bahwa buku saku ini layak dengan segi materi sebesar 87%, keterbacaan bahasa sebesar 91%, penyajian buku sebesar 90%, dan tampilan buku sebesar 91%. Secara keseluruhan, buku saku ini dianggap layakCopyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.